Computed Tomographic Perfusion Improves Diagnostic Power of Coronary Computed Tomographic Angiography in Women: Analysis of the CORE320 Trial (Coronary Artery Evaluation Using 320-Row Multidetector Computed Tomography Angiography and Myocardial Perfusion) According to Gender. (November 2016) - Penagaluri, Ashritha; Higgins, Angela Y.; Vavere, Andrea L.; Miller, Julie M.; Arbab-Zadeh, Armin; Betoko, Aisha; Steveson, Chloe; Zimmermann, Elke; Cox, Christopher; Rochitte, Carlos E.; Dewey, Marc; Kofoed, Klaus F.; et al.
Abstract : Background—: Coronary computed tomographic angiography (CTA) and myocardial perfusion imaging (CTP) is a validated approach for detection and exclusion of flow-limiting coronary artery disease (CAD), but little data are available on gender-specific performance of these modalities. In this study, we aimed to evaluate the diagnostic accuracy of combined coronary CTA and CTP in detecting flow-limiting CAD in women compared with men. Methods and Results—: Three hundred and eighty-one patients who underwent both CTA-CTP and single-photon emission computed tomography myocardial perfusion imaging preceding invasive coronary angiography as part of the CORE320 multicenter study (Coronary Artery Evaluation Using 320-row Multidetector Computed Tomography Angiography and Myocardial Perfusion) were included in this ancillary study. All 4 image modalities were analyzed in blinded, independent core laboratories. Prevalence of flow-limiting CAD defined by invasive coronary angiography equal to 50% or greater with an associated single-photon emission computed tomography myocardial perfusion imaging defect was 45% (114/252) and 23% (30/129) in males and females, respectively. Patient-based diagnostic accuracy defined by the area under the receiver operating curve for detecting flow-limiting CAD by CTA alone in females was 0.83 (0.75–0.89) and for CTA-CTP was 0.92 (0.86–0.97; P =0.003) compared with men where the area under the receiver operating curve for detecting flow-limiting CAD by CTA alone was 0.82 (0.77–0.87) and for CTA-CTP was 0.84 (0.80–0.89; P =0.29). Conclusions—: The combination of CTA-CTP was performed similarly in men and women for identifying flow-limiting coronary stenosis; however, in women, CTP had incremental value over CTA alone, which was not the case in men. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00934037. Abstract : Supplemental Digital Content is available in the text.